Using the nonlinear regression to predict the prices of stocks and its impact on the investor decisions in the financial market - kendory, Emad; Kareem, Nazar Abdul; Humadi, Saleh Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
Investing in stock is full of long risks which make it difficult to manage stock. Because of theses the different choices, investors can afford losses that it maybe accumulate, then it causes bankruptcy. Investors use the different approaches to predict the future prices of stocks. The non-linear regression is vital method to do that. The non-linear regression depends upon the historical data of stocks to expect the prices of the next period. For purposes of this topic, the research divided this study into four sections. The first section included the methodology of research and some of previous studies, the second section targeted on the theoretical framework of the research, the third section show the application of research, while the fourth section was devoted to the foremost vital conclusions and recommendations reached by the researcher. The study concludes that the equation of the non-linear regression passed through the data point, in others words the non-linear regression equation is the best fit for the data of study sample.